Penerapan Multirepresentasi Pada Pembelajaran Inkuiri Terbimbing Terhadap Penguasaan Konsep Dari Gaya Belajar - Indah Safitri; Ida Kaniawati; Heni Rusnayati (Department of Physics Education, Universitas Mataram, 2020)
This study aims to determine the increase in mastery of the concept of high school students after the implementation of a multi-representation approach to guided inquiry learning that has been adapted to student learning styles on Work material. The research method used was quasi experimental using one group pre-test post-test design. The research sample was students of class X MIPA 6 at one school in SMA Negeri in Bandung, totaling 36 students. The research instrument used was a test of mastery of the concept, a VARK learning style questionnaire, a student response questionnaire, and an observation sheet. Based on the findings of the paired t-test, the absolute value of t is 21.16 and t-table is 2.03, so H0 is rejected and Ha is accepted. The results of this research, there is a significant influence on the application of multi-representation approaches to guided inquiry learning that is adapted to studentÃ¢â¬â¢s VARK learning styles. Also seen the overall gain test results obtained a gain value of 0.561 in the medium category. The gain value obtained by students with kinesthetic learning style is greater than students who have visual, aural, read/write, and multimodal learning style, with a value of 0.584 in medium category. And the study group that gets the greatest gain is the learning group two and the learning group three with the gain value 0.612 with the medium category.